Predicting mobile use for big-event content: the role of active choice, habit and structure. (2019) - Tang, Tang; Cooper, Roger
Mobile technologies have substantially changed how people consume media content, in particular during big events. This study examined audience's mobile experience with the 'first mobile Olympics' and found that motivations, preference, perceived usefulness, access to media technologies, and media use routine significantly predicted mobile use for big-event content. Additionally, findings suggest that compared to nonusers, mobile Olympics users were more intensely engaged and involved in sports and the Olympics overall, enjoyed a broader range of Olympics sports, and were more accustomed to using online and mobile sources to view media content. Television was still the dominant platform for big-event viewing, however, mobile consumption increased dramatically during the London Olympics, and indicated a need for more personalised, multifaceted programming with mobility and immediacy.